2015
DOI: 10.14573/altex.1502041
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid human cell lines lack functional regulation of aryl hydrocarbon receptor-dependent phase I genes

Abstract: SummaryPrimary dendritic cells and myeloid cell lines are used to assess the skin sensitization hazard in in vitro approaches. The aryl hydrocarbon receptor (AhR) modulates expression of CYP enzymes, which play a significant role in the bioactivation of various xenobiotics. These studies revealed a strong constitutive expression of the AhR in primary human monocytes, monocyte-derived immature dendritic cells (iDC) and cord blood-derived Langerhans cells (LC). In contrast, mRNA and protein expression of AhR was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 43 publications
2
5
0
Order By: Relevance
“…We could show an increase in CYP1A and CYP1B1 expression in CD34LC upon treatment with the AhR ligand FICZ. This is in accordance with reports showing inducible expression of CYP1B1 in freshly isolated human LC after 7,12‐dimethylbenz[a]anthracene stimulation and induction of CYP1A1 in cord blood‐derived LC as well as in human monocytes and DC …”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…We could show an increase in CYP1A and CYP1B1 expression in CD34LC upon treatment with the AhR ligand FICZ. This is in accordance with reports showing inducible expression of CYP1B1 in freshly isolated human LC after 7,12‐dimethylbenz[a]anthracene stimulation and induction of CYP1A1 in cord blood‐derived LC as well as in human monocytes and DC …”
Section: Discussionsupporting
confidence: 93%
“…These cells were used to further analyze the role of AhR activation in skin APC. The AhR is expressed on CD34LC as reported . Furthermore, we could detect that the AhRR is also expressed in human CD34LC (Figure ).…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…Molecular studies also showed that the tolerogenic aryl hydrocarbon receptor pathway was activated. AhR expression levels vary in immune cells, with high expression levels found in monocytes, 82 dendritic cells, macrophages, 83 and B cells. 84,85 Within the T-cell compartments, T H 17 cells, and to a lesser extent Treg cells, express AhR.…”
Section: Discussionmentioning
confidence: 99%
“…On the other side, the AhR‐dependent signalling pathway is connected with other signalling pathways such as the antioxidant response by Nrf2 . Further on, the AhR interacts with several cytokines and growth factors including the epidermal growth factor depending signalling, TNF‐α and TGF‐β, and finally, the AhR is expressed also in immunocompetent cells such as antigen‐presenting monocytes or macrophages as well as T lymphocytes, in particular in Th17‐cells . Therefore, it ruled out that the AhR functions on the one side as a sensor not only for multiple exogenous chemical agents but also for UV light and the microbiome; on the other side, this receptor influences in the target organs such as the skin multiple physiological and pathophysiological processes, e.g.…”
mentioning
confidence: 99%